In Situ Molecular Architecture of the Helicobacter pylori Cag Type IV Secretion System - Bo Hu (American Society for Microbiology, 2019)
ABSTRACT Helicobacter pylori colonizes about half of humans worldwide, and its presence in the gastric mucosa is associated with an increased risk of gastric adenocarcinoma, gastric lymphoma, and peptic ulcer disease. H. pylori strains carrying the cag pathogenicity island (cagPAI) are associated with increased risk of disease progression. The cagPAI encodes the Cag type IV secretion system (CagT4SS), which delivers the CagA oncoprotein and other effector molecules into human gastric epithelial cells. We visualized structures of native and mutant CagT4SS machines on the H. pylori cell envelope by cryoelectron tomography. Individual H. pylori cells contain multiple CagT4SS nanomachines, each composed of a wheel-shaped outer membrane complex (OMC) with 14-fold symmetry and an inner membrane complex (IMC) with 6-fold symmetry. CagX, CagY, and CagM are required for assembly of the OMC, whereas strains lacking Cag3 and CagT produce outer membrane complexes lacking peripheral components. The IMC, which has never been visualized in detail, is configured as six tiers in cross-section view and three concentric rings surrounding a central channel in end-on view. The IMC contains three T4SS ATPases: (i) VirB4-like CagE, arranged as a hexamer of dimers at the channel entrance; (ii) a hexamer of VirB11-like Cagα, docked at the base of the CagE hexamer; and (iii) VirD4-like Cagβ and other unspecified Cag subunits, associated with the stacked CagE/Cagα complex and forming the outermost rings. The CagT4SS and recently solved Legionella pneumophila Dot/Icm system comprise new structural prototypes for the T4SS superfamily. IMPORTANCE Bacterial type IV secretion systems (T4SSs) have been phylogenetically grouped into two subfamilies. The T4ASSs, represented by the Agrobacterium tumefaciens VirB/VirD4T4SS, include “minimized” machines assembled from 12 VirB- and VirD4-like subunits and compositionally larger systems such as the Helicobacter pylori CagT4SS. T4BSSs encompass systems closely related in subunit composition to the Legionella pneumophila Dot/IcmT4SS. Here, we present structures of native and mutant H. pylori Cag machines determined by in situ cryoelectron tomography. We identify distinct outer and inner membrane complexes and, for the first time, visualize structural contributions of all three “signature” ATPases of T4SSs at the cytoplasmic entrance of the translocation channel. Despite their evolutionary divergence, the CagT4SS aligns structurally much more closely to the Dot/IcmT4SS than an available VirB/VirD4 subcomplex. Our findings highlight the diversity of T4SSs and suggest a structural classification scheme in which T4SSs are grouped as minimized VirB/VirD4-like or larger Cag-like and Dot/Icm-like systems.